2005
DOI: 10.1152/ajpregu.00850.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia after protein ingestion concurrent with injection of a GLP-1 receptor agonist in rats: a possible role for dietary peptides

Abstract: Protein ingestion after injection of the glucagon-like peptide-1 receptor agonist Exendin-4 (Ex-4) causes hyperglycemia in rats. The objectives of this study were to determine the components of protein digestion responsible for this effect and to associate it with changes in the concentrations of other metabolites and hormones. Two experiments were conducted. In the first experiment, food-deprived rats were gavaged with intact whey (WP) or albumin protein, their hydrolysates, amino acid mixtures (1 g/2.5 ml), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…A similar hyperglycemic effect was observed following an acute Ex-4 injection in fasted nondiabetic rats. One mechanism for this could be a Ex-4-induced sympathoadrenal activation (2,28). Consistent with this hypothesis, Ex-4 was shown to activate neurons in brain sites involved in autonomic and adrenal medulla controls (55).…”
Section: Discussionmentioning
confidence: 78%
“…A similar hyperglycemic effect was observed following an acute Ex-4 injection in fasted nondiabetic rats. One mechanism for this could be a Ex-4-induced sympathoadrenal activation (2,28). Consistent with this hypothesis, Ex-4 was shown to activate neurons in brain sites involved in autonomic and adrenal medulla controls (55).…”
Section: Discussionmentioning
confidence: 78%
“…In GK rats, after the transient decrease, glucose actually increased and remained at a high level until 2 h. Likewise, several other groups have observed that acute administration of exendin-4 causes hyperglycemia in multiple strains of rats (Aziz et al, 2005;PĂ© rez-Tilve et al, 2010). Extensive studies showed that acute administration of exendin-4 only lowered the glycemic response to glucose challenge in the early phase as a result of augmented early insulin secretion, and then induced hyperglycemia dose-dependently 15 to 30 min after drug administration without further increased insulin response (PĂ© rez-Tilve et al, 2010).…”
Section: Pk/pd Modeling Of Exendin-4 In Goto-kakizaki Ratsmentioning
confidence: 76%
“…However, the elevation of plasma glucose induced by Ex-4 was prevented by AP Ï© SFO lesion. Hyperglycemia following Ex-4 injection in fasted nondiabetic rats has been reported (3,34). The mechanism underlying this phenomenon would seem to involve the sympathoadrenal system.…”
Section: Discussionmentioning
confidence: 99%